Female Worker Problems : Skill Mismatch Versus Working Hours Mismatch - Jamalludin Jamalludin (Jurnal Aplikasi Statistika & Komputasi Statistik, 2020)
Female workers have a double burden, between work in the office and at home. Skill mismatch and working hours mismatch exacerbate the problems faced by female workers. This study aims to analyze the relationship between skill mismatch and working hours mismatch with the job satisfaction of female workers. This study used secondary data from Happiness Level Measurement Survey (SPTK) 2017. Indonesia Statistics office organized SPTK2017 at all Indonesian provinces with 72.317 respondents. Respondents in SPTK2017 are the head of the household or his/her couple. The unit of analysis in this study was female workers with a total of 21,805 observations.The analytical method used is descriptive analysis and multiple linear regression. The descriptive findings show that as many as 22.1 percent of female workers with skills mismatch and 27.85 percent of female workers working hours mismatch are not satisfied with the work they are doing. The regression findings show that skill mismatch and working hours mismatch is negatively related to women's job satisfaction. Working hours mismatch has the strongest relationship to women's job satisfaction among other variables in the model.